Sejarah Perkembangan Manajemen Mutu - Heri Triyanto; Hambali Bachtiar; M. Syahran Jailani; Harlina Harja (Journal on Education, 2024)
The history of the development of quality management has gone through a long and winding journey since this concept was first introduced. From its historical roots related to the industrial revolution to the modern era of globalization, this concept continues to develop and adapt to changes in the business and technological environment. This article provides a brief overview of the evolution of quality management, including the role of key figures such as W. Edwards Deming and Joseph M. Juran in introducing basic principles that are still relevant today. The history of quality management reflects a paradigm shift from traditional inspection approaches towards more holistic and sustainable approaches, such as Total Quality Management (TQM) and Lean Six Sigma. By understanding its development history, organizations can learn valuable lessons to improve the quality of their products and services in the future. The development of education quality management reflects the evolution of approaches and practices in an effort to improve the overall quality of education. By taking these factors into account, educational institutions can develop effective strategies to achieve higher learning goals for all students.